Role of CT Imaging for the Management of COVID-19 - Shahzeb Mastoi, Aneel Kumar, Tauqeer Anjum, Mahnoor Shahzeb, Mehak Gul, Rashid Daudpota (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: To evaluate the role of high-resolution Computer tomography imaging in the management of COVID-19. Study design: Prospective study Place and duration of study: Jinnah Postgraduate Medical Centre Karachi from 1st December 2021 to 31st May 2022. Methodology: One hundred patients suspected to be suffering from COVID-19 were enrolled. All patients underwent Reverse transcriptase-based polymerase chain reaction tests (RT-PCR). The patients were divided into positive or negative depending upon their test results. A high-resolution computed tomography scan was followed in every patient and the results were compared with the reverse transcriptase-based polymerase chain reaction tests findings. The sensitivity and Specificity of the CT scan test were assessed. Results: The mean age of the patients was 59±6.5 years. There were 60 (60%) male and 40 (40%) female patients. Around 58% of the patients were found as positive on PCR while 42% were negative. There 75% of the cases were positive for novel coronavirus on high-resolution computed tomography scan while only 25% were negative. Conclusion: Chest HRCT-scan proved to be a better and more sensitive tool for the diagnosis of novel coronavirus and can be considered as an alternative screening tool for COVID-19 confirmation. Keywords: SARS-CoV-2, Severity, Pulmonary, CT-scan, Serotype